(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the physical condition of South Sulawesi men’s pencak silat athletes who will participate in the National Student Sports Week (POMNAS). The study subjects amounted to 20 male athletes, who were tested through five physical components, namely speed, agility, muscle strength, leg explosiveness, and cardiovascular endurance (VO₂max). The data was analyzed using descriptive statistics to determine the minimum, maximum, mean, sum, and standard deviation (SD) values, and categorized into five levels of physical conditions: Very Poor, Less, Sufficient, Good, and Very Good. The results showed that the average physical condition of athletes was in the "Very Good" category, with some athletes (35%) in the "Very Good" category, 15% in the "Good" category, 25% in the "Sufficient" category, 20% in the "Less" category, and 5% in the "Very Less" category. The standout components are leg explosiveness and muscle strength, while speed, agility, and VO₂max still need to be improved. These findings show the inequality of physical ability between athletes and affirm the importance of a specific, structured, and needs-based physical training program to maximize athletes’ performance in POMNAS matches.